1988
DOI: 10.1101/gad.2.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of chicken vitellogenin I and III cDNAs and the developmental regulation of five estrogen-responsive genes in the embryonic liver.

Abstract: The isolation of cDNA clones that code for portions of the two minor chicken vitellogenin (VTG) genes (VTGI and VTGIII) is reported. These clones represent unique sequences that are expressed exclusively in the livers of estrogenized birds. In the liver of the egg-laying hen, the levels of RNAs encoding VTGI, VTGII, and VTGIII are approximately 11,000, 30,000, and 3,000 molecules per cell, respectively. We have used the newly isolated clones, as well as the yolk protein cDNAs previously available [VTGII, apoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…The ability to activate the apoVLDLII gene is acquired at the beginning of this period, and the efficiency with which the gene can be expressed increases markedly between days 10 and 13 (16,18). The mobility of the complex before day 13 is similar to the mobility of the complexes detected in extracts from nonhepatic tissues.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The ability to activate the apoVLDLII gene is acquired at the beginning of this period, and the efficiency with which the gene can be expressed increases markedly between days 10 and 13 (16,18). The mobility of the complex before day 13 is similar to the mobility of the complexes detected in extracts from nonhepatic tissues.…”
Section: Discussionsupporting
confidence: 51%
“…In the case of the apoVLDLII gene, the liver does not begin to display the ability to express the gene in response to treat-ment with estrogen until sometime between days 7 and 9 of embryogenesis, whereas the ability to activate expression of the vitellogenin genes is not acquired until 2 to 3 days later (11,16,18). Although dormant in roosters, chicks, and embryos, these genes can be activated in birds of either sex without a requirement for DNA replication (25).…”
mentioning
confidence: 99%
“…Vitellogenin genes have also been sequenced from frogs (9), nematodes (10), and insects (15), and a comparison of coding sequences revealed that, with the exception of the insect genes, the vitellogenin genes represent a very old and fairly well-conserved family (15). Thus our previous observation that a VTGIII cDNA clone failed to hybridize to any portion of the VTGII gene was somewhat surprising (6). To address more broadly the evolutionary relationship between the chicken VTGII and VTGIII genes, we first isolated overlapping genomic DNA clones which span the VTGIII gene (see below) and then hybridized each of these against each of three overlapping genomic clones which encompass the VTGII gene (4).…”
mentioning
confidence: 99%
“…1) indicates that the 3.5-kilobase (kb) EcoRI fragment from VTGIII clone X315 is similar to the 5.6-kb EcoRI fragment from VTGII clone X210. Likewise, the lone spot in panel 6 indicates that the same 3.5-kb EcoRI fragment from VTGIII clone X315 hybridizes to the 4.1-kb EcoRI fragment from VTGII clone X220. These results indicate that the central region of the VTGII gene, which encodes phos-vitin (12), is the only portion of the gene which is similar enough to hybridize to the VTGIII gene in this assay (see Fig.…”
mentioning
confidence: 99%
“…expressed as early as day 9 of embryonic development (16), whereas the VTGI gene cannot be maximally expressed until birds are 6 weeks of age (15). Since the level of estrogen receptors increases over this period (14,15), the different yolk protein genes may require distinct threshold levels of receptors for their maximal expression.…”
mentioning
confidence: 99%